PENERAPAN METODE PEMBELAJARAN MODELING THE WAY TERHADAP AKTIVITAS BELAJAR DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS II MI. MUHAMMADIYAH 2 SINGKAWANG - Nur'ain, Sherli; Anika Marhayani, Dina; Suprapto, Wasis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research animsto: 1) Determine the improvment in learning outcomes for class II MI. Muhammadiyah 2 Singkawang before and after applied the modeling the way learning method; 2) To determine the differencen in improving learning outcomes for class II MI students. Muhammadiyah 2 singkawang between the experimental class and the control class; 3) To find out the learning activities of class II MI students. Muhammadiyah 2 Singkawang is considered active when the modeling the way learning method is applied. The type or research used is quantitative using a quasi-experimental method (Quasi experimental design). The research design used was a quasi-experimental design with a pretest-posttest only group design applied to two groups. The population in this study were all class II MI Students. Muhamamdiyah 2 Singkawang for the 2023/2024 academic year, totaling 39 students, The sampling technicque that will be examined in this research is class II A And II B MI. Based on the result of the research and discussion in the previous chapter, it can be concluded that: (1) The results of calculating the studen’s pre-test and post-test score data obtained an N-Gain value of 0,51. This is indicated by the average N-Gain of 0,51 with medium criteria. (2) Based on data analysis carried out using parametric staticial tests, namely the T test, tcount> ttabel, it can be concluded that there is an increase in student learning outcomes. Based on data analysis carried out using parametric statistical test, namely the T test, tcount> ttabel. (3). Student learning activities are active when applying the modeling the way learning method. It can be seen from the results of calculating the score for each indikator, the pre-test is 63,94% and the post-test is 67,31. Meanwhile, the calculation of the score per indikator is that the overall average for the pre-test is 51,16 and the average for the post-test is 54,39.